Superior Vena Cava Syndrome in a Patient with Polycytemia Vera: Diagnosis and Treatment - Salvatore Lentini; Mario Barone; Filippo Benedetto; Francesco Spinelli (Cardiology Research and Practice)
Polycythemia vera is a myeloproliferative disorder characterized by thrombotic complications both in the arterial and venous systems. We report the case of a 55-year-old patient affected by polycythemia vera, presenting with acute superior vena cava syndrome due to thrombosis of the upper part of the superior vena cava. Diagnosis was done clinically and by computed tomography scan and showed an unusual finding: an air bubble trapped in the brachiocephalic venous trunk. The patient underwent emergency surgery. Diagnosis and treatment of the case are discussed.